LITERASI DAMAI: STRATEGI MENANGKAL RADIKALISME MELALUI CERITA DAN BUDAYA - Nurul Jannah Ramadhan; Resti Aulia; Putri Thamara Utami; Serlin Astria Togito S; Laila Nursalam; Lili Tazkiyyah; Zacri Alhafis; Nur Hayati (CV. Denasya Smart Publisher, 2026)
Radicalism poses a serious t social challenge to adolescents, particularly when values of tolerance are not firmly established. Normative educational approaches often prove ineffective, necessitating more contextual strategies. This community service activity aimed to instill peace values and raise awareness against radicalism among high school students through peace literacy using stories and cultural narratives. The program was conducted on November 27, 2025, at SMA Negeri 4 Pekanbaru, involving 45 students and eight facilitators from Universitas Muhammadiyah Riau. The method integrated peace literacy presentations with culturally relevant storytelling. The results demonstrated that this approach successfully captured students' attention and fostered an engaging learning atmosphere. Students showed improved understanding of tolerance and a stronger rejection of radical ideologies. In conclusion, peace literacy through stories and culture serves as an effective, interactive educational strategy to prevent radicalism in schools.